THE INFLUENCE OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE: (Study on Employees of PT. Pos Indonesia Jombang Branch) - Sari, Wahyu Wulan; Prasetyo, Deni Widyo (Transpublika Publisher, 2024)
The purpose of this study was to investigate and clarify the impact of job satisfaction and organizational commitment on the performance of employees at the PT Pos Indonesia Jombang Branch. Data was gathered through the distribution of surveys, interviews, observations, and documentation. A quantitative research method was employed, focusing on describing or providing an overview of the subject under investigation using collected data. A questionnaire was administered to 35 employees to collect data for this study. Explanatory research was the type of research utilized. The findings indicate that high job satisfaction can enhance the performance of employees at PT Pos Indonesia Jombang Branch. Similarly, good organizational commitment can improve the performance of PT Pos Indonesia Jombang Branch employees. The management of PT Pos Indonesia Jombang Branch is advised to continue to increase job satisfaction and strengthen employee organizational commitment through employee development programs, improving the work environment, and adequate recognition and rewards. These steps can contribute to improving employee performance and achieving organizational goals more effectively.